The strength of weak integrated information theory. Issue 8 (August 2022) - Mediano, Pedro A.M.; Rosas, Fernando E.; Bor, Daniel; Seth, Anil K.; Barrett, Adam B.
Abstract : The integrated information theory of consciousness (IIT) is divisive: while some believe it provides an unprecedentedly powerful approach to address the 'hard problem', others dismiss it on grounds that it is untestable. We argue that the appeal and applicability of IIT can be greatly widened if we distinguish two flavours of the theory: strong IIT, which identifies consciousness with specific properties associated with maxima of integrated information; and weak IIT, which tests pragmatic hypotheses relating aspects of consciousness to broader measures of information dynamics. We review challenges for strong IIT, explain how existing empirical findings are well explained by weak IIT without needing to commit to the entirety of strong IIT, and discuss the outlook for both flavours of IIT. Highlights: The integrated information theory of consciousness (IIT) is unprecedentedly ambitious in that it proposes a universal mathematical formula, derived from fundamental properties of conscious experience, to describe the quality and quantity of consciousness for any physical system that possesses it. IIT proponents believe it may solve the 'hard problem' of consciousness of why and how physical processes can be accompanied by subjective experience. However, in the current formulation, IIT formulae are not always well-defined and current empirical evidence does not support the level of specificity present in the theory. At the same time, available empirical evidence does support a weaker, less prescriptive version of the theory. We argue that distinguishing a 'weak' from a 'strong' flavour of IIT can provide a useful theoretical umbrella for ongoing empirical work, widening the overall appeal and applicability of the theory.